PENGARUH SERVICE QUALITY DAN WORD OF MOUTH TERHADAP REVISIT INTENTION YANG DIMEDIASI OLEH DESTINATION IMAGE PADA WISATA PANTAN TERONG ACEH TENGAH - Elvi Oktariani; Syafruddin Chan (Departemen Manajemen, 2019)
Abstract : This study aims to determine the effect of service quality and word of mouth on revisit intention mediated by the destination image. The sample consisted of 210 respondents who visited the Central Aceh pantan terong tour. The sampling technique uses the nonprobability sampling method with purposive sampling. Data collection is done through surveys with questionnaire methods. The data analysis technique used is sem using analysis of moment structure (AMOS) is a statistical method chosen to describe the observed variables. The results showed that service quality was not significant to revisit intention, word of mouth was not significant to revisit intention, service quality was not significant to revisit intention, word of mouth was not significant to revisit intention, destination image had no significant effect on revisit intention, there was a significan effect direct service quality towards revisit intention mediated by destination image, there is a direct effect of word of mouth on revisit intention mediated by destinasion image.